Development and Validation of Google Sites Technology-Assisted Student Worksheet to Increase Students' Collaboration Skills in Science Learning in Junior High School - Khumairoh, Nurista Yuliatul; Nuha, Ulin; Ahmad, Nur (Program Studi Pendidikan IPA, Universitas Islam Lamongan, 2025)
Development and Validation of Google Sites Technology-Assisted Student Worksheet to Increase Students’ Collaboration Skills in Science Learning in Junior High School. This research is based on the problem of collaboration skills of students in class VIII F SMP Negeri 6 Jember which is still low in science learning conducted by observation. One way to overcome this is to develop E-LKPD assisted by Google Sites to improve students' collaboration skills. The purpose of the study was to examine the validity, practicality, and effectiveness of E-LKPD assisted by Google Sites to enhance student collaboration skills in science learning. The research design uses Research and Development (R&D) with the Plomp development model which includes preliminary research, prototyping stage, and evaluation stage. Products that have been developed, get a validation score of 94% with a very valid category. Practicality is 96.83% with a very practical category. The effectiveness of E-LKPD is 63% with the results of the N-gain test with a moderate category, 77% self-assessment with a high category in collaboration, and 88% student response questionnaire with a very good category. The results of this study can conclude that E-LKPD assisted by Google Sites can be said to be valid, practical, and effective in learning science in junior high school.